Revealing Hedonism of Main Character as Seen in The Lorax Movie by Chris Renaud and Kyle Balda - Munandar, M Aris; Firdiansyah, Firdiansyah (Journal of Religion and Film, 2025)
Hedonism is a life style that becomes one of the idea depict in literature. Literature performed a picture of life and reality in social. The aims of this research is to describe the types of hedonism reflected toward main character in The Lorax movie by Chris Renaud and Kyle Balda, the factors that caused hedonism on main character portrayed in The Lorax movie by Chris Renaud and Kyle Balda, the effects of hedonism reflected toward main character in The Lorax movie by Chris Renaud and Kyle Balda. This research uses Weijers (2012) theory. This research employs descriptive qualitative research. The object of this research was in The Lorax movie by Chris Renaud and Kyle Balda. The data were collected by documentation technique Then, the data were analyzed by Hedonism theory and qualitative research.The findings of research show that; First, there are two types of hedonism reflected toward main character in the Lorax movie by Chris Renaud and Kyle Balda, value hedonism and hedonistic egoism. Second, there are two factors that caused hedonism on main character portrayed in The Lorax Movie by Chris Renaud and Kyle Balda, Individual’s Personality and Family. Third, there two effects of hedonism reflected toward main character in the Lorax Movie by Chris Renaud and Kyle Balda is Pleasure and Depression